The tax scenario in India: a macroeconomic outlook - Saikia, Moon; Bora, Meghna; Alom, Mahmudul; Bora, Deepa Moni; Mollick, Biki; Saikia, Mrinal (Przegląd Krytyczny, 2025)
The paper examines India’s long-term tax situation and analyses the factors contributing to the various stages of tax collection. The article’s primary focus is on the direct and indirect taxes, as well as their historical trajectory. Nevertheless, we assessed the relationships between various tax components and the nation’s macroeconomic indicators. The data contained in the article was gathered from reputable government agencies. Bar and line diagrams were utilized to examine the data, and a pair-wise correlation matrix was employed to investigate the relationship between the various tax components and macroeconomic indicators. The study shows that the percentage of taxes to GDP and the rate of indirect taxes to total taxes have been trending upward over time. GST has significantly aided the growth of the indirect tax share. Moreover, the research indicates that several macroeconomic variables correlate with various tax components.